1995
DOI: 10.1016/s0042-6822(95)80053-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of a second functional hairpin ribozyme against HIV-1

Abstract: We have constructed a hairpin ribozyme targeted to cleave a conserved sequence in the HIV-1 pol gene. The ribozyme was modified to include a structure-stabilizing tetraloop. In vitro studies revealed a cleavage efficiency unprecedented for hairpin ribozymes (Kcat/Km = 75 min-1 microM-1). Stable retroviral vector transduction of this ribozyme gene in T-cell lines resulted in long-term ribozyme expression. As compared to control vector transduced T-cells, the pol ribozyme-transduced cells exhibited significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…Previous work with hairpin ribozymes against HIV have revealed that adding a tetraloop to the loop 3 region can enhance the catalytic efficiency (k cat /K m ) of a ribozyme. 13 It is noteworthy that the addition of a tetraloop to either BR1 or BR3 increases the catalytic efficiency by increasing k cat , without significantly altering K m . Based on our studies with HIV, the in vitro catalytic efficiency of each ribozyme usually serves as a good indicator of its catalytic efficiency in cells (unpublished data).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous work with hairpin ribozymes against HIV have revealed that adding a tetraloop to the loop 3 region can enhance the catalytic efficiency (k cat /K m ) of a ribozyme. 13 It is noteworthy that the addition of a tetraloop to either BR1 or BR3 increases the catalytic efficiency by increasing k cat , without significantly altering K m . Based on our studies with HIV, the in vitro catalytic efficiency of each ribozyme usually serves as a good indicator of its catalytic efficiency in cells (unpublished data).…”
Section: Resultsmentioning
confidence: 97%
“…Some regions of a hairpin ribozyme can be modified for its optimized cleavage activity for each individual ribozyme. [9][10][11][12][13] those regions (Figure 1b). 12,13 Modification in the loop 3 ribozyme target site was chosen due to high sequence region of BR1 and BR3 resulted in improved RNA cleavconservation between different HBV strains.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations